Peningkatan Kompetensi Menggambar Teknik Digital Siswa SMK Melalui Pelatihan AutoCAD Berbasis Praktik Langsung - Rizky Simanjuntak; Ummu Salamah; Heri Franata Sitorus; Hindra Karamah Putra Handana; Anni Zahara Putri; Arrisha Anggraini (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Digital technical drawing competency based on AutoCAD proficiency represents an essential requirement for students pursuing construction-related vocational training to successfully transition into professional practice. This study reports on a community service intervention implemented at SMK Negeri 1 Lubuk Pakam, designed to systematically enhance students' competencies in digital technical drawing through hands-on AutoCAD training. The program engaged 26 Grade XI students specializing in Building Construction Engineering over a single training day. The instructional methodology integrated pre-assessment, instructor-led demonstration, structured laboratory-based practical training, and post-assessment evaluation. Comparative analysis of pre-test and post-test performance scores revealed substantive improvements in students' mastery of fundamental AutoCAD operations, 2D technical drawing procedures, layer organization protocols, and the application of technical dimensioning and annotation conventions. Qualitative feedback indicated that participants perceived the training as beneficial for their academic coursework completion and preparation for professional competency certification examinations. These findings substantiate the efficacy of intensive, hands-on AutoCAD training as a time-efficient and pedagogically sound intervention for advancing vocational students' technical competencies in digital drawing applications.